114 The types of ketogenic diets used at great ormond street hospital (GOSH). (22nd November 2019) - Simpson, Zoe; Eltze, Christin; Smith, Hannah; Bor, Bahee Van de; Urban, Victoria; McCullough, Fiona
Abstract : Background: Ketogenic diets (KD) are used as a treatment option for pharmacoresistant epilepsy. There are different types of KDs, which are variations on a high fat, low carbohydrate (CHO) and sufficient protein diet. The CKD is the strictest, using ratios of fat to CHO and protein. The MKD does not require accurate measurements of food. The MCTKD uses MCT fats to promote ketosis. The aim of the audit was to identify the use of the types KDs, retention and age ranges. Methods: A retrospective audit of patients who commenced the KD between 01/10/17 and 30/09/18. The database was used to identify the patients, types of KD, age and retention. Data was input in to Microsoft Excel and analysed. No ethical approval was required. Results: 40 children commenced on the KD. Eight patients commenced as an emergency, six were given CKDEN. The table describes the cohort diet type, age and retention. The reasons for ceasing KD included inefficacy (20%), adverse side-effects (10%) and non-adherence (10%). Four patients within the CKDEN died, related to their underlying condition. Discussion: The results show there is a movement away from the traditional KDs. Retention on the MKD was higher than that of the other KDs in this cohort, which is discussed seen as a benefit to using the MAD. The emergency admissions and research work will skew the KD used towards the CKD/CKDEN due to the necessity to achieve ketosis quickly and research protocols. Conclusion: At GOSH a variety of the KDs are used within clinical practice. This small audit shows that the MKD is adhered to with fewer patients stopping within year one. Further data are required comparing efficacy of the different KDs due to the varying resource requirement for carers and clinicians.